2012
DOI: 10.1063/1.4733987
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of atmospheric molecules by ice nanoparticles: Pickup cross sections

Abstract: Uptake of several atmospheric molecules on free ice nanoparticles was investigated. Typical examples were chosen: water, methane, NO x species (NO, NO 2 ), hydrogen halides (HCl, HBr), and volatile organic compounds (CH 3 OH, CH 3 CH 2 OH). The cross sections for pickup of these molecules on ice nanoparticles (H 2 O) N with the mean size ofN ≈ 260 (diameter ∼2.3 nm) were measured in a molecular beam experiment. These cross sections were determined from the cluster beam velocity decrease due to the momentum tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…The value ofC v was calculated similarly. The following heat capacity values for water and He at 100 • C and 1 bar were used 31 With the present experimental conditions, the initial water cluster beam speed (before any pick-up) was calculated to be about 1465 m/s which seems reasonable reflecting on previous measured values 27 .…”
Section: Estimating Salt Concentrationsupporting
confidence: 51%
See 2 more Smart Citations
“…The value ofC v was calculated similarly. The following heat capacity values for water and He at 100 • C and 1 bar were used 31 With the present experimental conditions, the initial water cluster beam speed (before any pick-up) was calculated to be about 1465 m/s which seems reasonable reflecting on previous measured values 27 .…”
Section: Estimating Salt Concentrationsupporting
confidence: 51%
“…Lengyel et al 27 found for water clusters with n = 260 that the pick-up cross-section σ p for all the studied dopant molecules is always larger than the geometric cross-section σ g = πr 2 n , where r n is the cluster radius. Measurements indicated for example for the pickup of water molecules on water cluster σ p /σ g = 2.5 and for HBr, σ p /σ g = 1.4.…”
Section: Estimating Salt Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of the water cluster heat capacities as a function of the cluster size are given in Table I Another possible source of error in numerical modeling are the cluster cross sections used for cluster-monomer and cluster-cluster collisions. 30,31 We used an empirical expression for the diameter d of water clusters,…”
Section: Flow Conditions and Numerical Parametersmentioning
confidence: 99%
“…Large (H 2 O) N clusters withN ≈ 10-10 3 represent laboratory model to mimic 5 important systems and processes, e.g., cloud particle and aerosol nucleation [4,5,6,7,8], chemistry and photochemistry on ice particles in atmosphere [9,10,11,12], processes in radiation chemistry [13], processes in chemistry and biology induced and controlled by solvent [14] etc. In many laboratory studies water clusters are detected by mass spectrometric methods.…”
Section: Introductionmentioning
confidence: 99%